PENGARUH PENGETAHUAN AWAL, MOTIVASI BELAJAR, DAN DUKUNGAN TEMAN SEBAYA TERHADAP KETERAMPILAN KEARSIPAN DIGITAL MELALUI KETERLIBATAN BELAJAR SEBAGAI VARIABEL MEDIASI PADA SISWA MPLB SMK NEGERI 1 PATI - Tri Puji Lestari; Tusyanah Tusyanah (STKIP Pesisir Selatan, 2026)
Digital archiving skills are crucial for vocational students to meet industry demands. This study, based on Bandura’s Social Cognitive Theory, examined the factors influencing digital archiving skills among 102 vocational students (Grade 11 MPLB) at SMK Negeri 1 Pati, using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate a moderate predictive model (R² for digital archiving skills = 0.514; R² for learning engagement = 0.540). Prior knowledge has a direct positive effect on digital archiving skills, while learning motivation and peer support do not show significant direct effects. The findings suggest that prior knowledge exerts a direct positive influence on digital archiving skills. On the other hand, neither learning motivation nor peer support had a significant direct effect. A key finding of this study is the role of learning engagement as a full mediator, wherein all three variables (prior knowledge, learning motivation, and peer support) significantly influence digital archiving skills through the mediating effect of learning engagement.